Kontribusi as-Suyuti Dalam Historiografi Tafsir al-Qur'an - Nilda Hayati Hayati (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
In the discourse of Qur’anic studies in general, the study of historiography of Qur’anic exegesis remains neglected. Up to now, scholars are still attempting to reconstruct the history of Qur’anic exegesis comprehensively. Related to this, some of the historiographical literature on Qur’anic exegesis are still waiting to be explored. This paper discusses the historiography of Qur’anic exegesis with special reference to Ṭabaqāt al-Mufassirīn, written by Jalāluddīn as-Suyūṭī (1445-1505 AD), a prolific Egyptian writer. This book is the first biographical dictionary to list and contain the historical account of the Qur’anic interpreters. It contains 136 biographical information of the Qur’anic interpreters from the ‘Abbasid period. Started with the brief explanation of the historiography of the Qur’anic exegesis, this paper tries to analyze the historical material in that book with quantitative approach based on certain aspects contained within. In addition to that, the research also explains the significance and contribution of the Tabaqāt al-Mufassirīn in the Qur’anic studies, particularly related to the effort to map out a comprehensive overview of the history of Qur’anic exegesis.